Developing learning in the context of playfulness: defining roles and responsibilities (Research, Society and Development, 2022)
The objective was to understand the role of play in the development of early childhood education, aiming to prove its importance from the integration of those involved in the teaching-learning process. Seeking how and whose responsibilities are in the education of children and how to develop this work in a pleasant and pleasurable way. To carry out this work, bibliographical research was used. Data collection was carried out through the Google Academic platform for the selection of articles, theses, monographs, ebooks and articles published in the period 2017-2021, which were related to the proposed theme, bringing a scientific basis on what is said by professors and researchers about the value of playfulness inside and outside the classroom and how those responsible for this learning can exercise their role with dedication, respect and responsibility. Showing the importance of developing knowledge in the context of playfulness, focusing on the child's intellectual development in the family, school and society environment, arising from how to teach in a playful way, enabling knowledge, creativity, social interaction and growth in an integral way, making these children active and transforming beings. This research showed that the result of this work, brings a great diversity of understanding about the playful in the child's life. Playful activities with technology help a lot in the learning process. It is by playing that children know their limitations, helping them in cognitive, psychomotor, social, affective and psychological development.